2015
DOI: 10.1177/0263774x15614175
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, transport infrastructure governance, and planning: lessons from the corporatization of port authorities in East Asia

Abstract: Substantial research posits that institutions do matter in port development, resulting in path-dependent reform process. However, issues remain unaddressed, notably on how and why institutions matter during such process under diversified developmental phases and geographical settings. This paper investigates, based on the experience of two major ports in East Asia, in what ways and to what extent political institutions have shaped the process of change, the main sources of path dependency, the conditions under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…As such, port development is largely dependent on the past decision and institutional structure over a long period of time (Notteboom, 2009). A similar conclusion was drawn in Tongzon, Ng and Shou (2015) who investigated impacts of political institutions on port governance in two main ports in East Asia, Singapore and Tianjin, China. The study confirmed the proposition that port governance was strongly associated with the implementation process dependent on the paths that were established by the broader institutional framework in which the economies developed.…”
Section: Path Dependency Theorysupporting
confidence: 76%
See 1 more Smart Citation
“…As such, port development is largely dependent on the past decision and institutional structure over a long period of time (Notteboom, 2009). A similar conclusion was drawn in Tongzon, Ng and Shou (2015) who investigated impacts of political institutions on port governance in two main ports in East Asia, Singapore and Tianjin, China. The study confirmed the proposition that port governance was strongly associated with the implementation process dependent on the paths that were established by the broader institutional framework in which the economies developed.…”
Section: Path Dependency Theorysupporting
confidence: 76%
“…Such historical data can be useful in forecasting future behaviour, and this is especially so in port development where path dependency is significantly present here (Tongzon, Ng and Shou, 2015;Notteboom, 2009). Path dependency refers to those initial decisions made by people or entities will influence or lead to respective later decisions.…”
Section: Figure 13 Conceptual Model For the Multiple Linear Regressionmentioning
confidence: 99%
“…These mechanisms may concern the functional role the studied institution gains in the broader context of co-existing institutions, the institution's legitimation when it is increasingly perceived as the only legitimate authority in its domain or how the institution distributes power among actors, as the dominant groups tend to support institutional settings that maintain and foster their power [40]. Path dependency analysis is applied also in land use and transport planning research [41][42][43][44][45][46][47][48][49][50].…”
Section: Analytical Approachmentioning
confidence: 99%
“…The discussion on Chinese seaport integration in terms of progress, dynamics, patterns and pathways, impacts, and institutional issues is evident (Notteboom, 2002;Ng et al, 2015; C. Wang et al, 2015;X. Wang et al, 2004;Notteboom & Rodrigue, 2008).…”
Section: Institutional Changes and Development In The Chinese Port Symentioning
confidence: 99%